2022
DOI: 10.3389/fgene.2022.1003964
|View full text |Cite
|
Sign up to set email alerts
|

Focus on long non-coding RNA MALAT1: Insights into acute and chronic lung diseases

Abstract: Acute lung injury (ALI) is a pulmonary illness with a high burden of morbidity and mortality around the world. Chronic lung diseases also represent life-threatening situations. Metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) is a type of long non-coding RNA (lncRNA) and is highly abundant in lung tissues. MALAT1 can function as a competitive endogenous RNA (ceRNA) to impair the microRNA (miRNA) inhibition on targeted messenger RNAs (mRNAs). In this review, we summarized that MALAT1 mainly parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 145 publications
0
7
0
Order By: Relevance
“…MALAT1 can worsen ALI conditions by interacting with different miRNAs [ 85 ]. MALAT1 can downregulate specific miRNAs and can ultimately facilitate the pathogenesis of ALI [ 86 ]. Overexpressed MALAT1 also sponges specific miRNAs, which can exacerbate inflammation.…”
Section: Lncrnas In Ali/ardsmentioning
confidence: 99%
See 1 more Smart Citation
“…MALAT1 can worsen ALI conditions by interacting with different miRNAs [ 85 ]. MALAT1 can downregulate specific miRNAs and can ultimately facilitate the pathogenesis of ALI [ 86 ]. Overexpressed MALAT1 also sponges specific miRNAs, which can exacerbate inflammation.…”
Section: Lncrnas In Ali/ardsmentioning
confidence: 99%
“…MALAT1 sponges miR-181a-5p by negatively regulating it. MALAT1 is overexpressed and miR-181a-5p is downregulated in ALI [ 86 ]. Either MALAT1 knockdown or miR-181a-5p overexpression reduces Fas and subsequently suppresses apoptosis and inflammation.…”
Section: Lncrnas In Ali/ardsmentioning
confidence: 99%
“…As one of the first lncRNAs discovered, metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) has been linked to the pathophysiology of inflammatory illnesses, metabolic diseases, and cancer [ 40 , 41 , 42 ]. As discovered by Gu et al [ 43 ], the early inflammatory response of acinar cells may include a “MALAT1-miR-194-yes-associated protein 1 (YAP1)” mutual feedback loop.…”
Section: Exosome-specific Ncrnasmentioning
confidence: 99%
“…8 The aberrant expression of lncRNAs has also been suggested to correlate with inflammatory lung diseases including COPD. 9,10 Liu et al identified many dysexpressed lncRNAs in the blood samples of patients with COPD via high-throughput RNA sequencing. 11 Zong et al reported that the lncRNA CCAT1 is overexpressed in COPD tissues, whereas its knockdown ameliorated cigarette smoke extract (CSE)-induced inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, lncRNA BC069792 functions as a tumor suppressor in breast cancer by upregulating Potassium Voltage‐Gated Channel Q4 through the adsorption of hsa‐miR‐658 and hsa‐miR‐4739 8 . The aberrant expression of lncRNAs has also been suggested to correlate with inflammatory lung diseases including COPD 9,10 . Liu et al identified many dysexpressed lncRNAs in the blood samples of patients with COPD via high‐throughput RNA sequencing 11 .…”
Section: Introductionmentioning
confidence: 99%